Application of Media-Assisted Concept Sentence Model to Improve Descriptive Paragraph Writing Skills of Grade IV Elementary School Students - Kiah, Delia Aminah; Sugiharti, Rini Endah; Rikmasari, Rima (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
A descriptive paragraph is a paragraph that describes an object, event, place, person or experience in detail.This study was conducted to improve the skills of writing descriptive paragraphs with the concept sentence method assisted by image media in grade IV students of SDN Marga Mulya I. This study was conducted with classroom action research through 2 cycle stages. This classroom action research was conducted because it was found that in grade IV students there were still many students who did not understand how to write paragraphs, students had difficulty developing the meaning they wanted to convey in writing and the use of learning methods that were less suitable. The results of this study prove that there was an increase in learning outcomes in the application of this model with a percentage of 66% of students who could in cycle 1 and increased to 80% in cycle 2 of students with descriptive paragraph writing skills. So the application of the concept sentence model assisted by image media is said to be successful in improving the skills of writing descriptive paragraphs in grade IV students of SDN Marga Mulya I.